The Impact Of Workload, Availability Of PPE Facilities And Organizational Support On The Work Stress Of Health Workers Taking Attention To Covid-19 Patients At RS Keluarga Kita - Stefano Leatemia; Agusdini Banun; Hasyim Hasyim (The Journal General Health and Pharmaceutical Sciences Research, 2023)
Since the outbreak of the corona virus-19 has made it difficult for all health workers and even lack of rest, causing many health workers to be vulnerable and easily experience stress at work. The purpose of this study was to assess the effect of workload, availability of PPE facilities and organizational support on the work stress of health workers who treat COVID-19 patients at our family hospital. This research was conducted from February 2021 to June 2021. The type of research carried out was explanatory research with quantitative methods. This research was conducted at the Kita Family Hospital with a total of 172 respondents. From the research conducted, it was found that there was an effect of workload, availability of PPE facilities, organizational support, and division of labor on the work stress of health workers who partially handle Covid-19, so it can be concluded that an even distribution of tasks and in accordance with competence will reduce stress. the work of health workers who handle Covid-19 during the pandemic by ensuring the availability of appropriate and sufficient PPE, providing good support, appreciating the efforts and work of health workers, paying attention to the welfare of health workers.